2020
DOI: 10.1177/0363546520960122
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Opioid Use Is a Risk Factor for Revision Surgery, Complications, and Increased Resource Utilization After Arthroscopic Rotator Cuff Repair

Abstract: Background: Studies have shown preoperative opioid use to influence outcomes after various surgical procedures. Researchers have not assessed this relationship after rotator cuff repair (RCR). Hypothesis/Purpose: The purpose of this study was to assess the relationship between preoperative opioid use and outcomes after arthroscopic RCR. We hypothesized that patients prescribed higher daily averages of preoperative oral morphine equivalents (OMEs) would show increased rates of 90-day complications and 3-year re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Our results suggested that preoperative opioid use may be associated with worsened perioperative pain and may lead to subsequent need for medical care. This relationship has been observed in open procedures such as hip and knee arthroplasty, as well as arthroscopic rotator cuff repair, where preoperative opioid use was associated with increases in postoperative complication rates, 4,6,17,26,38,45 postoperative narcotic consumption, 45 readmission, 6,26,58 revision, 5,17,26,52,58 costs, 6,17 and patient dissatisfaction. 19,51 The reasons for our findings are likely multifaceted and probably involve both physiologic and psychosocial factors.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results suggested that preoperative opioid use may be associated with worsened perioperative pain and may lead to subsequent need for medical care. This relationship has been observed in open procedures such as hip and knee arthroplasty, as well as arthroscopic rotator cuff repair, where preoperative opioid use was associated with increases in postoperative complication rates, 4,6,17,26,38,45 postoperative narcotic consumption, 45 readmission, 6,26,58 revision, 5,17,26,52,58 costs, 6,17 and patient dissatisfaction. 19,51 The reasons for our findings are likely multifaceted and probably involve both physiologic and psychosocial factors.…”
Section: Discussionmentioning
confidence: 74%
“…These cutoffs were selected in order to capture a diverse set of preoperative opioid dosing strategies, and they are similar to those previously reported in the literature. 17…”
Section: Methodsmentioning
confidence: 99%
“… 22 Recently, Farley et al. 23 showed that preoperative opioid use and increased dosage was a risk factor for postoperative complications and revision surgery. In our cohort, only 8.5% of patients used opioids preoperatively, and this had no association with postoperative pain management satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Beyond the greater societal consequences, excessive opioid use directly affects the hand surgeon’s daily practice. Farley et al 19 , 20 showed that preoperative opioid use was associated with poorer surgical outcomes and greater complication and revision rates in thumb carpometacarpal (CMC) arthroplasty and arthroscopic rotator cuff repair. Opioid misuse has been associated with increased overall morbidity (odds ratio, 2.3) and mortality (odds ratio, 3.7) after elective hand surgery.…”
mentioning
confidence: 99%